Unhealthy food consumption and its determinants among children aged 6–23 months in Bangladesh: insights from the Demographic and Health Survey 2022 - Rafid Hassan; Md. Shahadoth Hossain; Md. Jarif Mahbub; Md. Ruhul Amin; Sanjib Saha (BMC Public Health)
Abstract Background Low- and middle-income countries (LMICs), including Bangladesh, are experiencing a nutritional transition characterized by rising unhealthy food consumption (UFC), which increases the risk of nutrient deficiencies and chronic diseases in children. Despite this concern, research on UFC among Bangladeshi children aged 6–23 months is limited. Therefore, this study aims to estimate the prevalence and identify the factors contributing to UFC in this age group. Methods This study analyzed the Bangladesh Demographic and Health Survey (BDHS) 2022 dataset, including 2,499 children aged 6–23 months. UFC was defined as the consumption of sweetened beverages or sentinel unhealthy foods within the past 24 hours. Multivariate logistic regression was used to identify factors associated with UFC. Results The prevalence of UFC among children was 61.8%, with 49.2% consuming sentinel unhealthy foods and 31.4% consuming sweetened beverages. The strongest predictor of UFC was older child aged 18–23 months (AOR: 3.31, 95% CI: 2.55–4.32), and consuming minimum diversified diet (AOR: 2.50, 95% CI: 1.98–3.15). Other significant factors included recent morbidity (AOR: 1.24, 95% CI: 1.01–1.53), maternal employment (AOR: 1.36, 95% CI: 1.04–1.77), media exposure (AOR: 1.28, 95% CI: 1.02–1.59), and lower paternal education [primary (AOR: 1.72, 95% CI: 1.21–2.44); secondary (AOR: 1.58, 95% CI: 1.14–2.18)]. However, maternal decision-making power (AOR: 0.75, 95% CI: 0.58–0.96) and intended pregnancies (AOR: 0.76, 95% CI: 0.59–0.97) were associated with lower odds of UFC. Regional disparities were observed, with higher UFC prevalence in Dhaka, Khulna, Mymensingh, Rajshahi, and Rangpur. Conclusion The study highlights Bangladeshi children’s high prevalence of UFC, which demands public health interventions together with integrating behavior change communication into health, community and family-level services.